1990
DOI: 10.1523/jneurosci.10-01-00176.1990
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor produces fear-enhancing and behavioral activating effects following infusion into the locus coeruleus

Abstract: The present series of experiments tested the hypothesis that the behavioral activating and anxiogenic effects produced by intraventricular administration of corticotropin-releasing factor (CRF) may be mediated by noradrenergic neurons in the brain-stem locus coeruleus (LC). Results showed that infusion of CRF into the LC (100 ng) significantly increased nonambulatory spontaneous motor activity measured in photocell cages; ambulatory (i.e., locomotor) activity was not altered. In the modified Porsolt swim test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(145 citation statements)
references
References 45 publications
12
129
0
4
Order By: Relevance
“…This result is in accordance to the data from the other two CRH-Tg mouse lines (van Gaalen et al, 2002) (Dirks et al, 2001) and this finding was also in agreement with studies showing that icv CRH administration reduces immobility time in forced swimming in rats and it has been proposed that this may also be the result of increased anxiety (Butler et al, 1990).…”
Section: More Activity Exhibited By Cor-nes Mice In Forced Swimming Tsupporting
confidence: 92%
“…This result is in accordance to the data from the other two CRH-Tg mouse lines (van Gaalen et al, 2002) (Dirks et al, 2001) and this finding was also in agreement with studies showing that icv CRH administration reduces immobility time in forced swimming in rats and it has been proposed that this may also be the result of increased anxiety (Butler et al, 1990).…”
Section: More Activity Exhibited By Cor-nes Mice In Forced Swimming Tsupporting
confidence: 92%
“…There is a reciprocal relationship between the brain CRF and sympathetic systems, and CRH contributes to activation of the locus coeruleus during stress (Berridge and Waterhouse, 2003). Stress increases CRF concentrations in the locus coeruleus (Chappell et al, 1986), local application of CRF in the locus coeruleus induces behavioral activation (Butler et al, 1990), and i.c.v. administration of a CRF antagonist blunts the stress-induced increase in extracellular norepinephrine levels in the prefrontal cortex (Shimizu et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of CRF on LC firing rates can be desensitized by 1 or 5 days of prior (30 min) footshock stress (Curtis et al, 1995) or intracerebral application of CRF (Conti and Foote, 1996), indicating different responses of LC firing rates to CRF depending upon the quantity and quality of stressor exposure. The ability of CRF to induce behavioral correlates of fear and anxiety (defensive withdrawal) after intraventricular delivery is potentiated by infusion into the LC region (Butler et al, 1990) and two weeks of chronic, unpredictable stress produces increased concentrations of CRF in the LC of laboratory rats (Chappell et al, 1986). A CRF receptor antagonist applied to the LC attenuates the defensive withdrawal induced by prior immobilization (Smagin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of synthetic CRF into specific brain regions of several animal species elicits behaviors similar to fear and anxiety (Koob and Britton, 1990;Butler et al, 1990) and alteration of endogenous CRF concentrations has been demonstrated in several brain regions after chronic or acute exposure of laboratory animals to stressful stimuli that result in behavioral responses associated with fear and anxiety (Chappell et al, 1986;Bissette, 2001). Among these brain regions is the locus coeruleus (LC).…”
Section: Introductionmentioning
confidence: 99%